La Planeación Estratégica en la Gestión Administrativa de la Cámara de Comercio de la ciudad de Riobamba, periodo 2018. - Gloria Bethsabe, Vaca Holguín (2020)
The purpose of this research is to determine how the Strategic Planning affects the Administrative Management of the “Chamber of Commerce” in Riobamba,2018 period. For its fulfilment the study begins with the exposition of the theoretical elements on which the research was based, as well as the characterization of the “Chamber of Commerce”. Subsequently, the methodological elements of the study werw exposed, this being nun- experimental, transactional and descriptive in which techniques such as the interview and the survey were applied to a total of 322 members of the “Camara de Comercio” in Riobamba. Finally, the investigation culminates with the analysis of the results associated with the information collected, with ehich the SWOT Matrix of the “Chamber of Commerce” was established, evidencing a predominance in the interaction in the quadrant of weaknesses and threats, determining that the most negatively influential weakness in seizing opportunities as well as in the potentialization of threats is the absence of a Function Manual.